Column amounts of atmospheric HCOOH recorded by the FTIR stations Kiruna and Izana in the framework of the Network for the Detection of Atmospheric Composition Change (NDACC) ... - Hase, Frank; Blumenstock, Thomas; Schneider, Matthias (Karlsruhe Institute of Technology, 2023)
Messungen der Gesamtsäulengehalte von HCOOH in der Erdatmosphäre, gewonnen an den FTIR-Stationen Kiruna und Izana des NDACC (Network for the Detection of Atmospheric Composition Change). Der Izana Datensatz umfasst Messungen von 1999 bis 2015, der Kiruna Datensatz umfasst Messungen von 1996 bis 2015. ... : Column amounts of atmospheric HCOOH recorded by the FTIR stations Kiruna and Izana in the framework of the Network for the Detection of Atmospheric Composition Change (NDACC). The Izana dataset covers 1999 to 2015, the Kiruna dataset covers 1996 to 2015. ...